Search for electroweak production of supersymmetric particles in final states with two τ-leptons in s = 13 TeV pp collisions with the ATLAS detector - Aad, G.; Åkesson, T.P.A. ; 0000-0003-4141-5408; Doglioni, C.; Ekman, P.A. ; 0000-0002-7032-2799; Hedberg, V.; Herde, H. ; 0000-0001-8926-6734; Konya, B.; Lytken, E. ; 0000-0002-8141-3995; Poettgen, R. ; 0000-0002-3304-0987; Simpson, N.D.; Smirnova, O. ; 0000-0003-2517-531X; Zwalinski, L. (Journal of High Energy Physics, 2024)
Three searches for the direct production of τ-sleptons or charginos and neutralinos in final states with at least two hadronically decaying τ-leptons are presented. For chargino and neutralino production, decays via intermediate τ-sleptons or W and h bosons are considered. The analysis uses a dataset of pp collisions corresponding to an integrated luminosity of 139 fb−1, recorded with the ATLAS detector at the Large Hadron Collider at a centre-of-mass energy of 13 TeV. No significant deviation from the expected Standard Model background is observed and supersymmetric particle mass limits at 95% confidence level are obtained in simplified models. For direct production of χ~1+χ~1−, chargino masses are excluded up to 970 GeV, while χ~1± and χ~20 masses up to 1160 GeV (330 GeV) are excluded for χ~1±χ~20/χ~1+χ~1− production with subsequent decays via τ-sleptons (W and h bosons). Masses of τ-sleptons up to 500 GeV are excluded for mass degenerate τ~L,R scenarios and up to 425 GeV for τ~L-only scenarios. Sensitivity to τ~R-only scenarios from the ATLAS experiment is presented here for the first time, with τ~R masses excluded up to 350 GeV. © The Author(s) 2024.
Keywords: Beyond Standard Model; Electroweak Interaction; Hadron-Hadron Scattering; Supersymmetry